Storied Past, Bright Future: A Provenance Jam Session. Issue 1 (14th October 2022) - Bettivia, Rhiannon; Cheng, Yi‐Yun; Gryk, Michael; Bishop, Wade; Chassanoff, Alexandra; Greenberg, Jane; Lischer‐Katz, Zack
Abstract: This panel will explore provenance of the past, present, and future in information science and technology, as both a concept and professional and intellectual value. The OED defines "provenance" as origin, source, ownership of an artwork, or guidance to determine authenticity. Provenance today is not limited to history domains. It can be used to describe what did happen (retrospective provenance), what will happen (prospective provenance), and what could happen (subjunctive provenance). Provenance transcends disciplines, and this panel is intended for anyone who is interested in the world of provenance. Perhaps echoing life in general, provenance is more about the journey than the destination. The goal of the panel is not to find an authoritative answer to why we choose one method or theory of provenance over another. Rather, this "jam session" will empower participants‐ panelists, moderators, and audiences alike‐ to frame and answer provenance questions for their own work.